2016
DOI: 10.1063/1.4944390
|View full text |Cite
|
Sign up to set email alerts
|

Extreme ultra-violet burst, particle heating, and whistler wave emission in fast magnetic reconnection induced by kink-driven Rayleigh-Taylor instability

Abstract: A spatially localized energetic extreme ultra-violet (EUV) burst is imaged at the presumed position of fast magnetic reconnection in a plasma jet produced by a coaxial helicity injection source; this EUV burst indicates strong localized electron heating. A circularly polarized high frequency magnetic field perturbation is simultaneously observed at some distance from the reconnection region indicating that the reconnection emits whistler waves and that Hall dynamics likely governs the reconnection. Spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…Since the current and the background magnetic field are antiparallel in the axial direction, the jet kinks in a left-handed sense (Hsu & Bellan, 2003). The apparatus is described in detail in Hsu and Bellan (2002), Moser and Bellan (2012), and Chai et al (2016), and a 3-D magnetohydrodynamic simulation of the experiment is described in Zhai et al (2014). During the fast lateral acceleration of the growing helical perturbation, a secondary Rayleigh-Taylor instability develops on the trailing edge of the laterally moving jet.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the current and the background magnetic field are antiparallel in the axial direction, the jet kinks in a left-handed sense (Hsu & Bellan, 2003). The apparatus is described in detail in Hsu and Bellan (2002), Moser and Bellan (2012), and Chai et al (2016), and a 3-D magnetohydrodynamic simulation of the experiment is described in Zhai et al (2014). During the fast lateral acceleration of the growing helical perturbation, a secondary Rayleigh-Taylor instability develops on the trailing edge of the laterally moving jet.…”
Section: Methodsmentioning
confidence: 99%
“…This detachment necessarily involves a magnetic reconnection event due to the changing magnetic topology. Previous measurements of detachment events (Chai et al, 2016;Marshall et al, 2018) identified simultaneous emission of extreme ultraviolet light, X-rays, current disruptions, and broadband magnetic oscillations near the reconnection site. These reconnection events are not as reproducible as the global jet morphology, and occur for ∼60% of shots taken with a particular set of initial conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RT instability quickly erodes and breaks the jet structure, leading to fast magnetic reconnection. 20,24 Hydrogen plasmas are found to develop kink instability in a very similar manner; but no distinct RT instability has been observed for hydrogen jets with g $ 10 10 m/s 2 ; RT instabilities with axial wavelength k z ¼ 3 À 5 cm are observed only in some rare shots with strong lateral acceleration g ¼ 10 11 À 3 Â 10 11 m/s 2 . We name the two cases as type I and type II hydrogen jets, respectively.…”
Section: Introductionmentioning
confidence: 90%
“…There is jq 0 rÁ dU=ðcdqÞj $ jq 0 dU r =ðcRdqÞj $ 0:1 ( 1. Here, c $ 3 Â 10 6 s À1 , R¼3cm, dq $ q 0 based on recent Stark broadening spectroscopic measurement, 24 and dU r $ 10km/s estimated from Fig. 3 of Ref.…”
Section: Perturbation and Linearizationmentioning
confidence: 99%